2021
DOI: 10.1007/s40243-020-00186-2
|View full text |Cite
|
Sign up to set email alerts
|

Confine sulfur in double-hollow carbon sphere integrated with carbon nanotubes for advanced lithium–sulfur batteries

Abstract: The lithium–sulfur (Li–S) batteries are promising because of the high energy density, low cost, and natural abundance of sulfur material. Li–S batteries have suffered from severe capacity fading and poor cyclability, resulting in low sulfur utilization. Herein, S-DHCS/CNTs are synthesized by integration of a double-hollow carbon sphere (DHCS) with carbon nanotubes (CNTs), and the addition of sulfur in DHCS by melt impregnations. The proposed S-DHCS/CNTs can effectively confine sulfur and physically suppress th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Kim et al confined sulfur in carbon micropores and demonstrated 36% retention of capacity after 250 cycles [26]. Walle et al trapped sulfur in double hollow spheres to achieve 57% retention at a 0.2 C rate and 48 cycles [9]. Some of these findings are summarized in Table 1: During discharge, solid sulfur (S8) is reduced into a lithium polysulfide after dissolution in the electrolyte, which is reflected in a stepwise voltage discharge profile analogous to what is shown in Figure 3B (cycle 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kim et al confined sulfur in carbon micropores and demonstrated 36% retention of capacity after 250 cycles [26]. Walle et al trapped sulfur in double hollow spheres to achieve 57% retention at a 0.2 C rate and 48 cycles [9]. Some of these findings are summarized in Table 1: During discharge, solid sulfur (S8) is reduced into a lithium polysulfide after dissolution in the electrolyte, which is reflected in a stepwise voltage discharge profile analogous to what is shown in Figure 3B (cycle 2).…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been proposed to curb the transfer of resistive sulfide species to the anode or their dissolution into the electrolyte: engineering of the carbon surface with functional groups to chemically anchor the polysulfides to the carbon pores [1]; employing catalytic transition metal nitrides, sulfide, or oxides to increase the efficiency of the chain reaction [2,3]; or physical entrapment of sulfur into conductive matrices [4,5] to limit the deposition of resistive lithium sulfides at the anode. Previous efforts have shown that capacity degradation of the lithium-sulfur system stems from the higher discharge plateau [6], since that is where nonrecoverable products of the redox reaction involving long Energies 2024, 17, 2168 2 of 10 chain polysulfide are formed; therefore, efforts to create carbon-sulfur nanocomposites and the confinement of sulfur would cull the full reduction in polysulfide chain products, as wrapped sulfur sites would act as sites with limited lithium reactivity [7][8][9]. Additionally, encapsulation of recrystallized sulfur aims to circumvent drawbacks in the conventional methods of carbon-sulfur integration, namely, the limited effectiveness of the ball milling technique and the energy cost associated with the melt method [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations